MATHEMATICAL MODELING OF PRIMARY SOURCES OF INFORMATION USING THE STATISTICA SOFTWARE SYSTEM - Зінченко, В. П.; Зінченко, Н. П. (Proceedings of National Aviation University (archive), 2021)
The information technology of mathematical modeling of primary sources of information with the use of STATISTICA software system is considered. The advantage of the above is shownmethod compared to the traditional approach, which is based on the use of individual applications.